Analisis Yuridis Tentang Kekerasan Terhadap Anak Didik Di Sekolah Dasar Negeri 21 Padang Sidempuan - Lysha, Yeni; Marlina, Marlina; Muazzul, Muazzul (ARBITER: Jurnal Ilmiah Magister Hukum, 2021)
This study examines the violence against students in SD Negeri 21 Padang Sidempuan School conducted by teachers, school friends. The forms of violence experienced by students in leaming and learning process are physical and verbal violence, and protection received by students as victims who experience violence and juridical decision taken by the judge to the perpetrators of violence. This study aims to firstly understand the form of legal arrangements for children and teachers; secondly, to know the occurrence of violence against students in primary school Padang Sidempuan, Third, to analyze the application of juridical law by judges on the verdict number 747 / pid.sus / 2015 / Pn psp to perpetrators of violence against students. This study uses normatical juridical research that is to analyze and explain and analyze normative provisions related to the research content. The method used is descriptive analysis with approach to review verdict number 747 / pid.sus / 2015 / pn psps. Data were collected through document studies and literature relating to violence against students and regulations or legislation. Then the data in the analysis is qualitatively normative and interpreted. The results of this study indicate that: 1) the form of arrangements for children and teachers in teaching and learning process refers and guided by Law Number 20 of 2003 on National education system that is, in Article 4 which contains the principles of education and Article 12 contains the rights and obligations leamers. 2) other forms of violence against students in primary schools that are often accepted are discrimination, perpetrated by teachers, sexual assault such as his ass, mocked, physical abuse in the form of physical punishment such as pinched, thrown using chalk, markers towards the face of students, beaten Thighs with ruler. They perpetrate violence to their students by reason of no discipline, noisy in the classroom, not doing the exercises or homework (homework) and not discipline in studying in the classroom .. 3) The application of the law by the judge on the verdict number 747 / pid, sus / 2015 / Pn psp to the perpetrators of violence is fair because the judge only sentenced with imprisonment 3 months and the defendant did not undergo the confinement because the defendant has been serving the trial period for 6 months